Challenges Of Population Services Through Population Administration Information Systems In Jakarta Buffering Area - Gemiharto, Ilham; Rulandari, Novianita (Indonesian Scientific Publication, 2024)
The role of the population in driving economic growth and development is fundamental, functioning as an active consumer and contributor. An important foundation for informed policymaking and fostering smart citizens lies in the quality of human resources and the availability of accurate population data. The study addresses specific challenges within Jakarta's densely populated Buffer Area, particularly the urgent need for an updated population database. To address this problem, we propose a comprehensive Population Information System that integrates data from three provinces and nine districts/cities in the Greater Jakarta area, which includes geographic and demographic information. This integrated approach ensures the availability of real-time data for quick responses to population-related matters. The significance of our study is rooted in the constitutional mandate to regulate matters concerning Citizens and Residents, emphasizing the state's role in protecting human rights and providing legal certainty in Population Administration. We also emphasize important laws, including Law Number 24 of 2013 concerning Population Administration, protecting personal and legal status while facilitating data collection and utilization. Examining the various challenges facing population services in Jakarta's buffer city districts, focusing on local government initiatives and the Population and Civil Registration Office, is essential. Understanding these challenges and proposed solutions is critical to improving population services and promoting informed policymaking in this critical region. In addition, our findings underscore the urgent need for comprehensive reforms in Disdukcapil services, including addressing issues such as bribery and using the services of brokers who persist in administrative practices.